The Grinch Meets His Max - Bryan, Antonia D., 1946- (New York : Random House, 1998)
No matter what the Grinch does, he cant seem to rid himself of a friendly, playful puppy.
Keywords: Dogs -- Juvenile fiction; Human behavior -- Juvenile fiction; Easy readers, Juvenile